Determining the Targets of Fluopsin C Action on Gram-Negative and Gram-Positive Bacteria - Navarro, Miguel Octavio Pérez; Dilarri, Guilherme; Simionato, Ane Stefano; Grzegorczyk, Kathlen; Dealis, Mickely Liuti; Cano, Barbara Gionco; Barazetti, André Riedi; Afonso, Leandro; Chryssafidis, Andreas Lazaros; Ferreira, Henrique; Andrade, Galdino (Frontiers in Microbiology, 2020)
The antibiotic activity of metalloantibiotic compounds is evaluated since the 90’s and many different modes of action were characterized. In the last decade, the effect of secondary metabolites produced by Pseudomonas aeruginosa LV strain, including a cupric compound identified as Fluopsin C, were tested against many pathogenic bacteria strains, proving their high antibiotic activity. In the present study, the bactericidal mechanisms of action of Fluopsin C and the semi-purified fraction F4A were elucidated. The results found in electron microscopy (SEM and TEM) demonstrated that both Fluopsin C and F4A are affecting the cytoplasmatic membrane of Gram-positive and Gram-negative bacteria. These results were confirmed by fluorescence microscopy, where these bacteria presented permeabilization of their cytoplasmatic membranes after contact with the semi-purified fraction and pure compound. Using electronic and fluorescence microscopy, along with bacterial mutant strains with marked divisional septum, the membrane was defined as the primary target of Fluopsin C in the tested bacteria.